BETWEEN YOU AND WE: STRUCTURAL NARRATIVE ANALYSIS ON DOA YANG DITUKAR BY FADLI ZON - Susanto Susanto (Universitas Muhammadiyah Semarang, 2019)
One of political phenomena in 2019 in Indonesia is the polemics caused by a political poem by Fadli Zon (FZ) entitle Doa yang Ditukar (exchanged prayer) which was considered as mocking one of Nahdhatul Ulama Senior Clerics, Maemon Zubair known as Mbah Moen. There was unclear subject/ character of Kau (you) in the poem which was suspected as referred to Mbah moen. Indonesian Mass media made this situation worse by only discussed it politically and legally without ever touching language and literary discourse in their programs as means of social education. Therefore, in this study, the poem Doa yang Ditukar by Fadli Zon is analyzed from structural narrative point of view which sees poetry as narrative structure which its meaning is built by intrinsic elements. The result of this study shows that first the poem Doa yang Ditukar by Fadli Zon narrate about the struggle between we which refers to the narrator and pejuang istikomah and amanah and kau which refers to amoral government and its companions. Second it is hard to show that there is mockery made by the poem because there is no clear subject of kau refered to certain person in reality.